World Heritage lizard: population genetics and species status of the range-restricted Hamelin skink, Ctenotus zastictus - Singhal, Sonal; Solis, Elizabeth; Rabosky, Daniel L. (Bulletin of the Society of Systematic Biologists, 2022)
The Shark Bay World Heritage region in western Australia is home to a number of species of substantial conservation concern. Among these is a small scincid lizard, Ctenotus zastictus, which represents one of the most geographically-restricted vertebrates on the Australian mainland. The long-term persistence of Ctenotus zastictus is threatened due to the small size of its range, isolation from suitable habitat patches elsewhere, and potential impacts from climate change and mining. Accordingly, conservation efforts in Australia have targeted C. zastictus as the focus of protection. But this attention might be unwarranted – the species might not be evolutionarily unique. Previous genetic assessments have suggested limited differentiation between C. zastictus and its putative sister taxon, and the taxonomic status of C. zastictus has never been formally evaluated. Here, we use population genomic, phylogenetic, and ecoclimatic analyses to characterize the species status of C. zastictus in context of its closely-related congeners. In doing so, we explore the practical and conceptual challenges of revising species boundaries in threatened species, many of which are also rare and range-restricted. We demonstrate that C. zastictus is a coherent evolutionary unit that has been isolated from its putative sister species for at least two million years. Based on these results, we recommend that C. zastictus should retain its taxonomic status.